Anal human papillomavirus infection: a comparative study of cytology, colposcopy and DNA hybridisation as methods of detection. Issue 1 (February 1991) - Sonnex, C; Scholefield, J H; Kocjan, G; Kelly, G; Whatrup, C; Mindel, A; Northover, J M
Abstract : OBJECTIVE--To compare anal cytology, colposcopy and DNA hybridisation as methods of detecting anal HPV infection. SUBJECTS AND DESIGN--Patients attending: (1) a genitourinary medicine (GUM) clinic with ano-genital warts; (2) a surgical out-patient department with anal fissure or haemorrhoids were examined for evidence of anal HPV infection. RESULTS--Considering GUM clinic attenders, 17% (38/225) and 40% (90/225) had perianal or anal canal warts respectively. Colposcopic examination revealed anal acetowhite lesions without warts in 28% (63/225). Cytological evidence of HPV infection was found in 98%, 83%, and 90% of patients with anal canal warts, perianal warts and acetowhite lesions respectively. Anal intraepithelial neoplasia (AIN) was documented in 22% of patients with anal canal warts compared with 6% with perianal warts (p less than 0.01). HPV DNA was detected from the anal brushings of 71%, 50%, 32%, and 29% of patients with anal canal warts, perianal warts, acetowhite lesions and a normal anal examination respectively. HPV type 6/11 was detected in the majority of HPV positive samples. Considering surgical out-patient attenders with no history or signs of anal warts, 25% showed cytological evidence of anal HPV infection and HPV DNA was detected from anal brushings in 3% (2/71). CONCLUSION--Anal examination with the colposcope is a useful method for detecting subclinical HPV infection. Anal cytology may prove helpful for detecting AIN, however, since koilocytosis was rarely seen, the specificity of the cytological criteria for anal HPV infection in the absence of AIN is uncertain. DNA analysis of anal brushings proved only moderately sensitive.